Unmanned aerial vehicles and aviation safety: a qualitative study - Uzuntas, K. N.; Aslan, M. (Cambridge Univ Press, 2025)
Technological developments and affordable price structures have increased the usage of unmanned aerial vehicles (UAVs) across almost all sectors, hence increasing demand. Since UAVs can fly and perform various tasks without requiring a human operator, the most dangerous and time-consuming tasks previously performed by humans in many sectors are now accomplished by using UAVs. The increased use of UAVs has also introduced critical safety and security risks, including airspace congestion, collisions and malicious use, and therefore, identifying and assessing the risks associated with UAVs and finding ways to mitigate them is of great importance. This qualitative study investigates the safety and security risks posed by the increased use of UAVs and discusses ways to mitigate these risks. Semi-structured interviews with aviation professionals, including pilots, air traffic controllers and academicians, were conducted, and the collected data were analysed by using MAXQDA 24 qualitative analysis software. The results indicate that 86% of participants emphasised air traffic density as a major safety concern, while 71% underlined the need for dedicated air corridors and robust legal frameworks to reduce collision risks. These insights suggest that the safe integration of UAVs into current aviation systems demands a multifaceted strategy involving regulatory interventions, such as clearly defined UAV flight zones and essential technological enhancements. Overall, the study underscores the urgent need for coordinated efforts-legal, technological, and inter-institutional-to ensure the secure incorporation of UAVs into national airspace.
Keywords: Uav; Safety; Security; Risk; Risk Assessment